2020
DOI: 10.1177/0144739420915758
|View full text |Cite
|
Sign up to set email alerts
|

Master of Public Administration and Master of Public Policy degrees: Differences and similarities in the curricula and course contents

Abstract: The historical origins of public administration and public policy analysis suggest that Master of Public Administration and Master of Public Policy programs should have different focuses in their curricula: the former on management skills and the latter on analytical skills. To investigate whether and to what extent the two types of programs are different and whether the accreditation standards of the Network of Schools of Public Policy, Affairs, and Administration have a homogenizing effect on them, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…There have also been discussions on analyzing the program design of MPA/MPP programs (Morç€ ol et al, 2020) and the inclusion of data science and information technology components for the MPA/MPP curriculum (McQuiston and Manoharan, 2021;Overton and Kleinschmit, 2022). In our study, we attempt to amalgamate a suitable curriculum for MPA/MPP programs that can reasonably accommodate the essential courses for the programs and with an option to include a data science/information technology focus.…”
Section: Background and Methodologymentioning
confidence: 99%
“…There have also been discussions on analyzing the program design of MPA/MPP programs (Morç€ ol et al, 2020) and the inclusion of data science and information technology components for the MPA/MPP curriculum (McQuiston and Manoharan, 2021;Overton and Kleinschmit, 2022). In our study, we attempt to amalgamate a suitable curriculum for MPA/MPP programs that can reasonably accommodate the essential courses for the programs and with an option to include a data science/information technology focus.…”
Section: Background and Methodologymentioning
confidence: 99%
“…Research methods courses were found in all NASPAA MPA and MPP programs sampled in a recent survey (Morçöl et al, 2020), evidencing a common avenue for integrating DSLF competencies into curriculums. Implementation of traditional research components varies widely, from literature review courses, consolidated research and statistics courses, to sequences with distinct courses in data analysis and research design.…”
Section: Recommendations For Pa Curriculumsmentioning
confidence: 96%
“…Information technology courses are only present in 16.3% of public administration academic programs (Morçöl et al, 2020), complicating the implementation of technical competencies. Until accreditation standards are implemented with a focus on technical competency, specialized coursework in information technology will be intermittent across programs.…”
Section: Recommendations For Pa Curriculumsmentioning
confidence: 99%
“…Our focus was the Master's degree programs in public administration in the Ural State University of Economics. The content of the programs was determined based on Russian standards and requirements, taking into account foreign experience [11][12][13].…”
Section: The Quality Assessment System In the Russian Federation Is Bmentioning
confidence: 99%